IMPROVING GEOGRAPHY BASIC KNOWLEDGE THROUGH THE SAINTIFIC APPROACH USING GEOGRAPHICAL CATALOG MEDIA - Widiyati, Ana (Indonesia University of Education, 2017)
The breadth of factual and conceptual dimensions of knowledge on geography material is still a problem that often leads to learners find it difficult to understand the concept of basic knowledge of geography covering the entire surface of the earth. One effort to improve the mastery of basic knowledge of geography by learning activities through a scientific approach to using learning resources and media of interest that is quickly geography. In this learning activity, learners are encouraged to find and search for answers to a variety of phenomena in the concept of basic knowledge of geography. Steps learning is done through scientific approaches include observing, ask, gather information, process and communicate information. Based on the steps of the scientific media catalog learners compose the geography of the various sources that are used as a medium of learning in improving the mastery of basic knowledge of geography. These include the assessment of learning through journal attitude assessment, assessment of knowledge through observation of knowledge and skills through the performance appraisal. In the aspect of attitude shows the results of positive attitudes. While the results for the assessment of knowledge and skills have reached, the criteria set at 76%. As a facilitator-teachers are expected to always create a learning atmosphere to encourage students to explore the environment and find their own answers to the knowledge that is being studied.